Restricted feeding improves performance of growing steers during subsequent grazing on native flint hills pasture - Anglin, C.O.; Epp, M.P.; Derstein, R.D.; Barnhardt, B.B.; Blasi, Dale A.; Olson, K. C.; Reinhardt, Christopher D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Beef stocker operators are margin-operators, and rising feed costs force them to consider alternative feeding strategies to reduce production costs. Limit-feeding is a management technique that has positive implications for cost control. In this experiment, we restricted dry matter intake to determine if steers could compensate for a period of dietary restriction during intensive early grazing. This study illustrated that limit-feeding could reduce feed costs for stocker and background operators.
Keywords: Beef; Cattle; Restricted dry matter intake